Factors affecting employees’ job involvement in fast food industry - Gan, Chia Seng; Hew, Woon Xin; Kong, Yuet Tong; Tam, Yun Chin (2011)
Employees’ job involvement has been found decreasing over the change of time. Therefore, the issue relates with employees’ job involvement is getting concern from other researchers due to lack of previous studies done for it. The purpose of this research is to investigate the factors (motivation, personal factor, training and job characteristic) that affect fast food restaurant employee job involvement in Malaysia. In this research project, we have used quantitative method which is questionnaire in order to collect data from the respondents. Questionnaires were administered in fast food restaurant in Kuala Lumpur, Penang, Johor (namely, Johor Bahru), and Perak (namely, Ipoh and Kampar). Besides, questionnaires also distributed to fast food employees (McDonald, Pizza Hut, KFC) by using close-ended question method. We have used Pearson correlation coefficient to analyses 380 responses from the questionnaires we obtained. In addition, multiple regressions revealed that the four sources of factors (motivation, personal factor, training and job characteristic) had significant positive relationship with employee job involvement in Malaysia.